Gravid uterus in a neglected incisional hernia: a rare case report - Raut, Rohini R.; Bhattacharya, Rangan; Murde, Snehal G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Incidence of incisional hernia in pregnancy is rare and is mainly managed conservatively. An ideal technique for repairing incisional hernia in pregnant patients has yet to be established, but it is clear that each case must be dealt with on an individual basis. It is essential for surgeons to consider the length of the surgery, the presence of contamination, the age of the fetus, the size of the defect, and the chances of recurrence before selecting which technique to employ when repairing abdominal wall hernia in pregnancy. We report a case of term pregnancy in a third gravida, aged 30 years with previous two vaginal deliveries with incisional hernia with overlying hyperpigmented lax skin patch. Incisional hernia developed as a complication because of the previous surgical history of open appendectomy 10 years back which was complicated in the post-operative period, 22 days later leading to an emergency laparotomy in view of intestinal obstruction. Caesarean section was done with simultaneous repair of the incisional hernia with nonabsorbable sutures. The post-operative recovery was uneventful.